Partnership for International Development: Finland–Argentina Conference on Circular Economy and Bioeconomy with Emphasis on Food Sovereignty and Sustainability - Raheem, Dele (2022)
A joint collaboration between the Cuarto region of Argentina championed by the National University of Rio Cuarto and the Arctic Centre of the University of Lapland, Finland organised a conference on several topics that are related to food sovereignty, sustainability, circular economy and bioeconomy. The efficient utilisation of natural resources in both regions is an important theme in meeting the sustainable development goals agenda. Hence, this partnership between the partner institutions will lead to the cocreation of knowledge. The topics were multidisciplinary, and the discussion focussed on research and teaching opportunities for institutions in both countries. The experts from both countries will continue to engage on the possibility of promoting the research agenda in these important areas.